INNOVATIVE PRACTICES IN SUPPLY CHAIN MANAGEMENT AND THEIR CONTRIBUTIONS TO REDUCE THE ENVIRONMENTAL IMPACT - Persike, Miriane Roberta; de Oliveira Ramos, Davyd Wesley; Drohomeretski, Everton (Caderno PAIC, 2017)
The objective of the present study was to identify the main innovative practices that have been used in Supply Chain Management. To achieve it was adopted in the Phase 1 as a methodological approach a systematic literature review, based on a content analysis of 58 articles that were published in periodicals, qualified by CAPES between 2008 and 2016. For Phase 2, it was sought to identify through a web research which of the established innovations on Phase 1 were used in some of the greatest Supply Chains, ranked by Gartner (2016). After the data collect of Phase 1, the findings were classified according to Ohio Model, innovation type and they received the attribution of the sustainable practice impact. In relation to Phase 2, the collected data were categorized into their respective organizations, as well they received the proper identification of the practices listed by Innovations Model, established by the authors. As a result of Phase 1, the Innovations Model was proposed, the data found indicated that most of the innovations are Incremental. For Phase 2, it was possible to admit that, compared to the Innovations Model, the organizations presented an average of 6.67 innovations stipulated in the construct.